No Sex Last Night: The Look of the Other - McFadden Wilkens, Cybelle (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2006)
In 1992, Calle departed briefly from still photography and experimented with video to create another version of herself as artist in No Sex Last Night (made in collaboration with Greg Shepard). Video is another way to construct herself for others and through others as she wants to be seen. No Sex Last Night differs from Calle's other projects due to her loss of artistic control, since Shepard also holds a video camera. Each camera reveals not only the perspective of the person shooting, but also shows the reactions and feelings of the other person being recorded. The interplay between the two cameras suggests that ways of looking at others and one's daily life are shaped by a need to be affirmed by the other. Calle affirms herself both as an artist and as a woman in this confrontation with the other, in this case, Shephard.